LA TAFOFLORA DE LA FORMACION MOJON DE HIERRO (GRUPO TEPUEL) EN LA LOCALIDAD ARROYO GARRIDO, PALEOZOICO SUPERIOR, PROVINCIA DE CHUBUT (Ameghiniana, 2013)
A new late paleozoic taphoflora from the Mojón de Hierro Fonnation at Arroyo Ganido (Chubut province) is described. The fossil plants were found in two sections stratigraphically about 500 m aparto In the lower section(pS 1)the folIowing taxa were identified: Bumbudendron sp.,Paracalamites austra lis ,Botrychiopsis sp., Nothorhacopteris majar nov. sp., Eusphenoteris cf. obtusiloba and Calymmatotheca sp. In the upper plant-bearing section (PS 11)Asterotheca piatnitzkyi, A. sp. Pecopteris sp., Sphenopteris sp., Glossopteris wilsonii, Eucerospermum cf. nitens and Cordaites sp. are described. Taphocenosis from PS 11es clearly linked to the Lubeckense flora al the Río Genoa Formation, and is included in the Ferugliocladus Superzone of a regional Lubeckian age (early Permian), On this base, and taking into account compositional and stratigraphic aspects, a pre-Lubeckian (i.e. late Carboniferous) age is suggested for the taphocenosis of the PS 1. This new finding improves the late Palaeozoic floristic record in Patagonia.